Balloon-Occluded Retrograde Transvenous Obliteration (BRTO) Versus Transjugular Intrahepatic Portosystemic Shunt (TIPS) for Treatment of Gastric Varices Because of Portal Hypertension: A Systematic Review and Meta-Analysis. Issue 7 (August 2020) - Paleti, Swathi; Nutalapati, Venkat; Fathallah, Jihan; Jeepalyam, Sravan; Rustagi, Tarun
Abstract : Background: Although gastric variceal (GV) bleeding is less common than esophageal variceal bleeding, the severity of GV bleeding is often greater with higher morbidity and mortality rates. Minimally invasive endovascular treatments such as balloon-occluded retrograde transvenous obliteration (BRTO) and transjugular intrahepatic portosystemic shunt (TIPS) have been used for the management of GVs with varying results, and individual and institutional differences exist in the use of BRTO and TIPS. We performed a systematic review and meta-analysis to compare the feasibility, efficacy, and safety of BRTO and TIPS for the treatment of GVs because of portal hypertension. Methods: Searches of PubMed, EMBASE, Google Scholar, and Cochrane Library databases were performed from inception through March 2019. Summary odds ratio (OR) with 95% confidence intervals (CI) was estimated for technical success, hemostasis rate, postprocedural complications, rebleeding rate, incidence of hepatic encephalopathy, and mortality rate at 1 year utilizing a random-effects model. Results: Seven studies with a total of 676 patients (BRTO: 462 and TIPS: 214) were included. There was no difference in pooled technical success rate (OR, 0.87; 95% CI, 0.28-2.73; P =0.81), hemostasis rate (OR, 2.74; 95% CI, 0.61-12.26; P =0.19), and postoperative procedure-related complications (OR, 1.95; 95% CI, 0.44-8.72; P =0.38). However, treatment with BRTO was associated with lower rates of postoperative rebleeding (OR, 0.30; 95% CI, 0.18-0.48; P <0.00001), postoperative encephalopathy (OR, 0.06; 95% CI, 0.02-0.15; P  < 0.00001), and mortality at 1 year (OR, 0.43; 95% CI, 0.21-0.87; P =0.02). Conclusions: BRTO was associated with lower rates of rebleeding, postprocedure hepatic encephalopathy, and mortality at 1 year. BRTO should be considered first-line modality for the treatment of GVs because of portal hypertension. Abstract : Supplemental Digital Content is available in the text.